Road freight transport decoupling: A comparative analysis between the United Kingdom and Spain - Alises, Ana; Vassallo, Jose Manuel; Guzmán, Andrés Felipe (Elsevier, 2014)
Economic growth has traditionally been linked to road freight transport demand, leading to a steady rise in social and environmental impacts. Concern about this problem has caused the EU to promote a decoupling strategy aimed at boosting sustainable development in European countries by improving the efficiency of transport systems without curbing economic growth. Over the last few years empirical evidence in some countries such as the United Kingdom has shown an increase in GDP while the volume of road freight traffic has remained stable or even decreased. This paper compares recent decoupling trends by analyzing the evolution of road tonne-kms/GDP relationship in the United Kingdom and Spain from 1999 to 2007. This comparison seeks to identify the main differences and key drivers of decoupling in both countries. We first provide an overview of the divergences between both economic structures and levels of road transport intensity. Then we conduct a decomposition analysis in order to identify the variables that explain the evolution of truck traffic per unit of GDP in each country. The results show that the increasing share of services in GDP has substantially contributed to decreasing road transport demand in both cases. Changes in road transport intensity due to improvements in logistic and supply chain management have been more successful in the UK than in Spain.

El crecimiento económico ha estado tradicionalmente vinculado a la demanda de transporte de mercancías por carretera, lo que ha dado lugar a un aumento constante de los impactos sociales y medioambientales. La preocupación por este problema ha llevado a la UE a impulsar una estrategia de desvinculación destinada a impulsar el desarrollo sostenible en los países europeos mediante la mejora de la eficiencia de los sistemas de transporte sin frenar el crecimiento económico. Durante los últimos años, la evidencia empírica en algunos países, como el Reino Unido, ha mostrado un aumento del PIB, mientras que el volumen del tráfico de mercancías por carretera se ha mantenido estable o incluso ha disminuido. Este artículo compara las tendencias recientes de desacoplamiento mediante el análisis de la evolución de la relación tonelada-km de carreteras/PIB en el Reino Unido y España desde 1999 hasta 2007. Esta comparación busca identificar las principales diferencias y los impulsores clave del desacoplamiento en ambos países. En primer lugar, proporcionamos una visión general de las divergencias entre las estructuras económicas y los niveles de intensidad del transporte por carretera. Luego realizamos un análisis de descomposición para identificar las variables que explican la evolución del tráfico de camiones por unidad de PIB en cada país. Los resultados muestran que la creciente participación de los servicios en el PIB ha contribuido sustancialmente a la disminución de la demanda de transporte por carretera en ambos casos. Los cambios en la intensidad del transporte por carretera debido a las mejoras en la gestión logística y de la cadena de suministro han tenido más éxito en el Reino Unido que en España.
Keywords: Transporte por carreteras - Aspectos económicos - Reino Unido; Road transport - Economic aspects - United Kingdom; Transporte por carreteras - Aspectos económicos - España; Road transport - Economic aspects - Spain; Desarrollo sostenible - España; Desarrollo sostenible - Reino unido; Sustainable development - United Kingdom; Sustainable development - Spain; Road freight transport; Decoupling; Economic structure; Road freight transport intensity